PERANCANGAN APLIKASI VIDEO EDUKASI PENYAKIT MENULAR PADA PUSKESMAS BETUNGAN BERBASIS ANDROID - Deddy Abdullah; Muhammad Ro’ouf Katin; Ujang Juhardi (Jurnal Media Infotama, 2023)
Infectious disease is a disease that is very feared, it is not uncommon for someone who is exposed to an infectious disease to get different treatment from the people around him. There are still many people who have not implemented or do not know how to prevent the spread of infectious diseases. Android is a Linux-based operating system that includes an operating system and middleware. Open source facilities can be freely developed for users. The Betungan Health Center is a health service located in the Betungan area, Bengkulu City, Bengkulu Province. Puskesmas is one of the government agencies engaged in public health services at the sub-district level. Educational video applications can make it easier for the public to find information and ways to deal with infectious diseases.